Community Structure of Bivalve in the Mangrove Ecosystem in the Apar Pariaman Village, Pariaman Utara Sub-district, Sumatera Barat Province - Nidanul Akmal Ritonga; Adriman Adriman; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstract Mangrove ecosystem in the Apar Village inhabited by numerous aquatic organisms, including bivalve.A research aim to determine the community structure of bivalve in the mangrove ecosystemhas been conducted on July 2019. There was 2 station, with 3 plots/station and 5 subplots/plot. In each subplot, the bivalve were collected by hand. Result shown that there was 3 species of bivalve, namely Polymesoda erosa, Geloina erosa, and Geloina expansa.The diversity index (H’) was 0,681-1,356, the uniformity index (E’) was 0.061-0.453 and the dominance index (C’) was 0.433-0.703. There was 5 species of mangrove, namely Sonneratia alba, Sonneratia caseolaris, Achantus ilicifolis,Nypa fruiticansandRhizophora apiculata. The water quality were as follows :temperature : 26-320C; soil temperature 29-33; pH7; soil pHwas 5-6 and Salinity was 4-22 ‰. Keywords: Geloina expansa, mangrove density,diversity index, dominance index